2012
DOI: 10.1111/j.1464-410x.2012.11373.x
|View full text |Cite
|
Sign up to set email alerts
|

Application technique: placement of a prostate–rectum spacer in men undergoing prostate radiation therapy

Abstract: E 6 4 7What ' s known on the subject? and What does the study add? Different spacing agents have been tested to reduce incidential radiation exposure of the rectum during radiotherapy to the prostate. These agents all had certain drawbacks; either the created space was too small or the agents used did not stay in place during radiotherapy treatment.The study describes the transperineal injection technique of a spacing agent in detail. Furthermore it shows the safety and effi cacy of the spacing hydrogel used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 30 publications
3
80
2
4
Order By: Relevance
“…It should be noted that whilst a number of clinical studies have reported hydrogel spacers to be safe [3,6], one published case report linked a rectal ulcer to a hydrogel insertion [28] and their use was halted in a recent trial, where two rectal fistulas were presumed due to the gradual accumulation of gel within the confines of the anterior rectal wall, as seen on magnetic resonance imaging during the course of the treatment [29]. However, the latter publication reported that in addition to gel migration, variations in individual patient radiosensitivity could have played a role, on-treatment image guidance was limited to orthogonal x-rays (it did not state whether alignment based on bony anatomy or prostate fiducials), and the in vivo dose to the anterior rectal wall was not known precisely [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that whilst a number of clinical studies have reported hydrogel spacers to be safe [3,6], one published case report linked a rectal ulcer to a hydrogel insertion [28] and their use was halted in a recent trial, where two rectal fistulas were presumed due to the gradual accumulation of gel within the confines of the anterior rectal wall, as seen on magnetic resonance imaging during the course of the treatment [29]. However, the latter publication reported that in addition to gel migration, variations in individual patient radiosensitivity could have played a role, on-treatment image guidance was limited to orthogonal x-rays (it did not state whether alignment based on bony anatomy or prostate fiducials), and the in vivo dose to the anterior rectal wall was not known precisely [29].…”
Section: Discussionmentioning
confidence: 99%
“…Injected hydrogel spacers (SpaceOAR, Augmenix Inc.) typically result in a separation of approximately 1 cm between the rectum and prostate [3]. This separation remains stable over 10-12 weeks [4] enabling substantial rectal dose reductions in the 60-70 Gy region [5].…”
mentioning
confidence: 99%
“…All hydrogel and fiducial marker placement were performed during the same outpatient procedure under local perineum skin numbing, following general application technique guidelines previously published 20. Specifically, at our facility, all patients had a fleet enema 2–3 h prior to the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The mean rectal IMRT doses per fraction were reduced from 1.05 to 0.74 Gy with hyalform (Wilder et al 2011). Hatiboglu et al (2012) analyzed 27 patients receiving hydrogel injection with regard to space creation, stability of spacer, duration of procedure, and reduction of rectal dose for prostate cancer patients receiving IMRT up to 78 Gy. Before hydrogel insertion the mean space between prostate and rectum was about 5 mm compared to about 15 mm after insertion, resulting in a space creation of 10 mm.…”
Section: Reproducibility/stability and Radioprotection Of The Rectum/mentioning
confidence: 99%